Analysis of Social Policies and Intervention Strategies for Mental Health Among Adolescents in Australia - Kumari, Priya; Singh, Vikram; Harrison, Liam (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2024)
Adolescent mental health is a growing concern in Australia, with various social, environmental, and academic pressures exacerbating anxiety, depression, and stress. This research aims to identify the key mental health challenges faced by Australian adolescents and evaluate the effectiveness of existing social policies in addressing these issues. The study focuses on factors such as social media influence, family dynamics, access to community resources, and the school environment. A mixed-methods approach was employed, including surveys from mental health organizations and interviews with policymakers and psychologists across major Australian cities like Sydney, Melbourne, and Perth, conducted between April 2023 and March 2024. Findings reveal that social media, peer pressure, and academic stress significantly contribute to adolescent mental health issues, with rural areas experiencing limited access to services and heightened stigma. Policy initiatives like Beyond Blue and Headspace are effective but show gaps in outreach to marginalized groups and lack of integration with educational systems. The study recommends improving outreach in rural areas, enhancing mental health professional training, and fostering partnerships between schools and mental health services. Future research should explore the long-term impacts of these recommendations and focus on sustainable solutions for digital health interventions, while also addressing cultural sensitivities and unique community needs in mental health service provision for adolescents.